Green Global Movement and Global Souths Development Dilemma: Case of Brazil, India, and South Africa - Majid, Marenda Athallah Farras (Yayasan Putroe Ceudah Aceh, 2025)
This study examines the challenges and structural intricacies of sustainable development in the Global South, with an emphasis on Brazil, India, and South Africa. Although these nations have considerable renewable energy potential and natural resources, their green development paths are inconsistent due to ongoing governance deficiencies, policy discrepancies, and socio-economic inequalities. The research employs a qualitative comparative approach to illustrate how external demands from the global green movement, mostly influenced by Global North agendas, frequently conflict with local realities, hence strengthening reliance and constraining developmental autonomy. The results indicate that although there are advancements in renewable energy adoption and conservation policy, the overall green transition is hindered by institutional fragmentation and the historical legacies of extractivism. Therefore, the green development in the Global South necessitates a reevaluation of global sustainability frameworks to align with regional contexts and aspirations. The study enhances current discussions by providing a refined comprehension of structural imbalances in global environmental governance.